The Conflicts Between Two Generations Reflected in Thank You Music Video - SORAYA, NISSA (LANTERN (Journal on English Language, Culture and Literature), 2016)
A song by MKTO which entitled “Thank You” is used by the writer to analyze its music video. The purpose of this study is to do a research about the conflicts between the old and young generation, which is related with social and symbolic power. Theories that are used are textual and contextual theories. The textual theory is used to analyze the verbal aspects (lyrics), aural aspects (music), and visual aspects (clips). Meanwhile the contextual theory is used to analyze the social issues which become the source of the conflicts